Brand Awareness Mediation: Analysis of Online Customer Reviews and Influencer Marketing on Local Perfume Purchase Decisions in E-Commerce - Cristian Pondra; Abdul Basit Al Firdaus; Intan Nurlita Sari; Agustina, Agustina (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims to determine the influence of online customer reviews and influencer marketing mediated by brand awareness on purchasing decisions for local perfumes in e-commerce. Quantitative methods were used in this research with a sampling technique using a purposive sampling method. The population in this study involved Gen Z and millennials with an age range of 17-40 years who were perfume customers in the city and district of Cirebon. The sample used was 150 respondents who met the research sample criteria. Data analysis in the research was processed using structural equation modeling (SEM-PLS) using the SmartPLS 4.1.0 application. Based on the results of the analysis of validity tests, reliability tests, discriminant validity, r-square tests, and path coefficients, results were obtained which stated that there was a positive and significant influence of each exogenous variable, namely Online Customer Reviews, Influencer Marketing on purchasing decisions. Furthermore, Brand Awareness can be a positive mediator in the correlation between Online Customer Reviews and Influencer Marketing which simultaneously influences Purchase Decision variables for local perfume products in e-commerce.